PENGARUSUTAMAAN MODERASI ISLAM (PENGUATAN NILAI-NILAI ISLAM INKLUSIF BAGI DAI DAN MUBALIGH DI SUMATERA BARAT) - Gazali Gazali; Endri Yenti (Turast: Jurnal Penelitian dan Pengabdian, 2022)
The issue of radicalism at this time has caused elements of society to try to prevent it. The Ministry of Religion in 2019 published the book Religious Moderation as a guide in carrying out and carrying out moderate religious orders. Universities under the Ministry of Religion also jointly carry out movements such as seminars, workshops and training for each element of higher education so that they become an indicator in the performance achievement of each level of office. The Tri Dharma of Higher Education also did not escape and participated in smoothing the moderation effort. Community service which is one of the Tdi Dharma Colleges participates in strengthening inclusive Islamic values for preachers and missionaries in West Sumatra. It is hoped that from this service, preachers and missionaries can understand religious moderation and become their mainstream in preaching among the people. From the service programs carried out, it can be seen that most of the preachers and missionaries understand religious moderation well. In connection with the results of a survey by the Ministry of Religion and equivalent to the Institute on the index of harmony and tolerance in West Sumatra which is below average, it is necessary to introspect and sit down with all stakeholders so that there will be changes in the future.